Vulnerability and access to care for South Asian Sikh and Muslim patients with life limiting illness in Scotland: prospective longitudinal qualitative study - Bhopal, Raj; Worth, A; Irshad, T; Brown, D; Lawton, J; Grant, E; Murray, S; Kendall, M; Adam, J; Gardee, R; Sheikh, A (My University, 2009)
Objectives To examine the care experiences of South Asian Sikh and Muslim patients in Scotland with life limiting illness and their families and to understand the reasons for any difficulties with access to services and how these might be overcome. Design Prospective, longitudinal, qualitative design using in-depth interviews. Setting Central Scotland. Participants 25 purposively selected South Asian Sikh and Muslim patients, 18 family carers, and 20 key health professionals. Results 92 interviews took place. Most services struggled to deliver responsive, culturally appropriate care. Barriers to accessing effective end of life care included resource constrained services; institutional and, occasionally, personal racial and religious discrimination; limited awareness and understanding among South Asian people of the role of hospices; and difficulty discussing death. The most vulnerable patients, including recent migrants and those with poor English language skills, with no family advocate, and dying of non-malignant diseases were at particularly high risk of inadequate care. Conclusions Despite a robust Scottish diversity policy, services for South Asian Sikh and Muslim patients with life limiting illness were wanting in many key areas. Active case management of the most vulnerable patients and carers, and "real time" support, from where professionals can obtain advice specific to an individual patient and family, are the approaches most likely to instigate noticeable improvements in access to high quality end of life care. Improving access to palliative care for all, particularly those with non-malignant illnesses, as well as focusing on the specific needs of ethnic minority groups, is required.
Keywords: ethnicity